Abū Bakr Ibn al-'Arabī (d. 543/1148) (Leiden ; Boston)
xi, 247 sayfa
Keywords: “Gathering the proceedings of a symposium organized on the occasion of the 900th anniversary of the qḍi ibn al-Arabi's (d. 543/1148) passing, this volume brings together a diverse array of contributions highlighting his legacy, his relationship with his master al-Ghazli (d. 505/1111), his unparalleled role in the transmission of Islamic knowledge in al-Andalus, and his lasting impact on various disciplines, including ḥadith, theology, Islamic law, Quranic exegesis, legal theory, grammar, adab, and Sufism. This book, written by internationally recognized scholars, not only commemorates the scholarly legacy of Ibn al-; Arabi but also illustrates how his intellectual teachings have shaped the landscape of Islamic thought in the Western Muslim world. Proudly, this book is the most accomplished reference bringing together recent advances on ongoing research around the qḍi Ibn al-'Arabi. Composed of articles written in English, Arabic and French, it will be of interest to specialists as well as the general public keen to learn more about the intellectual history of al-Andalus. Contributors Mohammed Aalouane, Ilyass Amharar, Noureddine Elhmidy, Maribel Fierro, Kenneth Garden, Abdelghani Idaikal, Delfina Serrano-Ruano, Bruna Soravia, Jaafar Ben El Haj Soulami, and Abdallah Taourati.“ --